2019
DOI: 10.1007/s00018-019-03227-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 17β-HSD12, the 3-ketoacyl-CoA reductase of long-chain fatty acid synthesis, on breast cancer cell proliferation and migration

Abstract: Metabolic reprogramming of tumor cells involves upregulation of fatty acid (FA) synthesis to support high bioenergetic demands and membrane synthesis. This has been shown for cytosolic synthesis of FAs with up to 16 carbon atoms. Synthesis of long-chain fatty acids (LCFAs), including ω-6 and ω-3 polyunsaturated FAs, takes place at the endoplasmic reticulum. Despite increasing evidence for an important role of LCFAs in cancer, the impact of their synthesis in cancer cell growth has scarcely been studied. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 80 publications
1
6
0
Order By: Relevance
“…S2B). The >180-kDa band might be the aggregated form of the ELOVL5 proteins, as suggested in a previous study showing that this protein aggregates during boiling (29). Similarly, we could detect ELOVL5 protein at ∼30 kDa in all mesenchymal-type GCs using unboiled lysates (Fig.…”
Section: Elovl5 and Fads1 Expression Is Up-regulated In Mesenchymal-typesupporting
confidence: 82%
“…S2B). The >180-kDa band might be the aggregated form of the ELOVL5 proteins, as suggested in a previous study showing that this protein aggregates during boiling (29). Similarly, we could detect ELOVL5 protein at ∼30 kDa in all mesenchymal-type GCs using unboiled lysates (Fig.…”
Section: Elovl5 and Fads1 Expression Is Up-regulated In Mesenchymal-typesupporting
confidence: 82%
“…HSD17B12 encodes an enzyme that controls elongation of long-chain fatty acids. Knockdown of HSD17B12 has been reported to either stimulate or inhibit cell proliferation ( 39 ). PEPD encodes pepdidase C, which cleaves di- and tripeptides containing carboxyl-terminal proline and is involved in protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“… (Nagasaki et al 2009 ) Knockdown of HSD17B12 increased proliferation and migration of MCF7 and MDA-MB-453 cells. (Tsachaki et al 2020 ) Knockdown of HSD17B12 decreased proliferation of SUM159 cells. (Tsachaki et al 2020 ) Ovarian cancer HSD17B12 expression in cancer tissue was suggested as a marker of poor prognosis.…”
Section: Enzymes Involved In Vl-pupa Synthesis In Crcmentioning
confidence: 99%
“… (Tsachaki et al 2020 ) Knockdown of HSD17B12 decreased proliferation of SUM159 cells. (Tsachaki et al 2020 ) Ovarian cancer HSD17B12 expression in cancer tissue was suggested as a marker of poor prognosis. Silencing of HSD17B12 in cancer cell lines resulted in growth inhibition and increased apoptosis.…”
Section: Enzymes Involved In Vl-pupa Synthesis In Crcmentioning
confidence: 99%